Synthesis and applications of graphitic carbon nitride (g-C3N4) based membranes for wastewater treatment: A critical review. Issue 1 (January 2023) - Qamar, Muhammad Azam; Javed, Mohsin; Shahid, Sammia; Shariq, Mohammad; Fadhali, Mohammed M.; Ali, Syed Kashif; Khan, Mohd. Shakir
Abstract: Semiconducting membrane combined with nanomaterials is an auspicious combination that may successfully eliminate diverse waste products from water while consuming little energy and reducing pollution. Creating an inexpensive, steady, flexible, and diversified business material for membrane production is a critical challenge in membrane technology development. Because of its unusual structure and high catalytic activity, graphitic carbon nitride (g-C3N4) has come out as a viable material for membranes. Furthermore, their great durability, high permanency under challenging environments, and long-term use without decrease in flux are significant advantages. The advanced material techniques used to manage the molecular assembly of g-C3N4 for separation membrane were detailed in this review work. The progress in using g-C3N4-based membranes for water treatment has been detailed in this presentation. The review delivers an updated description of g-C3N4 based membranes and their separation functions and new ideas for future enhancements/adjustments to address their weaknesses in real-world situations. Finally, the ongoing problems and promising future research directions for g-C3N4-based membranes are discussed.